C3-induced release of neurotrophic factors from Schwann cells – potential mechanism behind its regeneration promoting activity. (November 2015) - Rohrbeck, Astrid; Stahl, Frank; Höltje, Markus; Hettwer, Timo; Lindner, Patrick; Hagemann, Sandra; Pich, Andreas; Haastert-Talini, Kirsten
Abstract: Previous studies revealed a peripheral nerve regeneration (PNR) 1 promoting activity of Clostridium botulinum C3 2 exoenzyme or a 26 mer C-terminal peptide fragment covering amino acids 156–181 (C3 156−181 ), 3 when delivered as one-time injection at the lesion site. The current study was performed to 1) investigate if prolonged availability of C3 and C3 156−181 at the lesion site can further enhance PNR in vivo and to 2) elucidate effects of C3 and C3 156−181 on Schwann cells (SCs) 4 in vitro . For in vivo studies, 10 mm adult rat sciatic nerve gaps were reconstructed with the epineurial pouch technique or autologous nerve grafts. Epineurial pouches were filled with a hydrogel containing i) vehicle, ii) 40 μM C3 or iii) 40 μM C3 156−181 . Sensory and motor functional recovery was monitored over 12 weeks and the outcome of PNR further analyzed by nerve morphometry. In vitro, we compared gene expression profiles (microarray analysis) and neurotrophic factor expression (western blot analysis) of untreated rat neonatal SCs with those treated with C3 or C3 156−181 for 72 h. Effects on neurotrophic factor expression levels were proven in adult human SCs. Unexpectedly, prolonged delivery of C3 and C3 156−181 at the lesion site did not increase the outcome of PNR. Regarding the potential mechanism underlying their previously detected PNR promoting action, however, 6 genes were found to be commonly altered in SCs upon treatment with C3 or C3 156−181 . We demonstrate significant down-regulation of genes involved in glutamate uptake ( Eaac1, 5 Grin2a 6 ) and changes in neurotrophic factor expression (increase of FGF-2 7 and decrease of NGF 8 ). Our microarray-based expression profiling revealed novel C3-regulated genes in SCs possibly involved in the axonotrophic (regeneration promoting) effects of C3 and C3 156−181 . Detection of altered neurotrophic factor expression by C3 or C3 156−181 treated primary neonatal rat SCs and primary adult human SCs supports this hypothesis. Highlights: C3 and C3 156−181 altered gene expression profiles in Schwann cells. C3 and C3 156−181 induced changes in neurotrophic factor expression by Schwann cells. Prolonged availability of C3 or C3 156−181 in low doses did not support regeneration.